Leading Community Based Changes in the Culture of Health in the US Experiences in Developing the Team and Impacting the Community - Fernandez, Claudia S. P.; Corbie-Smith, Giselle (IntechOpen, 2021)
Advancing health equity calls for a new kind of leader and a new approach to leadership development. Clinical Scholars and Culture of Health Leaders are mid-career leadership development programs supporting the emergence of collaborative and systemic approaches, bringing teams of leaders together with others in the community to work toward the common goal of lessening health disparities. In each chapter of this book, the authors share how they tackled seemingly intractable issues, making headway through applying the principles of adaptive leadership in unbounded systems to create not only outcomes but also impacts on health disparities and, in some cases, sustainable and scalable applications. In this volume, you will learn how Clinical Scholars and Culture of Health Leaders programs curated and measured the successful learning and development of these dedicated health-equity advocates.